The Frostless Improvement and Feasibility Analysis of Cooling and Dehumidifying System in Mine Rescue Chamber - Yin Yue; Du Kai; Zhou Ronghui; Sun Changjian (Zhileng xuebao)
Powerless self-driven mine rescue chamber supplies essential survival conditions for the people who are trapped during mine accidents. As the evaporator in the CO2 cooling and dehumidifying system of current rescue chamber has frosting problem, an idea of frostless improvement of the cooling and dehumidifying system is proposed and the equipment structure and working process of the developed system are introduced in this paper. Then, the principle and feasibility of the frostless improvement are analyzed in detail. Furthermore, a control method which uses temperature hierarchical control group valves is stated, and several regulative methods of the system under variable load conditions are analyzed. The results provide reference for further study of mine rescue chamber.